2020
DOI: 10.1002/ncp.10593
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Mid‐Upper Arm Circumference in Diagnosing Malnutrition in Children With Cystic Fibrosis

Abstract: Background: Standardized diagnostic indicators for malnutrition using growth percentile z-scores (weight for length or body mass index [BMI]) and mid-upper arm circumference (MUAC) z-scores are being used in clinical practice; however, their application to the pediatric cystic fibrosis (CF) population is not well described. In this study, we aim to compare growth percentile z-scores and MUAC z-scores in diagnosing and classifying malnutrition in children with CF and assess the relationship between their degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Most of the studies suggest that attaining a BMI below the 10th percentile (roughly corresponding to a z-score < −1.0) is indicative of malnutrition. With this in mind, published data suggest that malnutrition prevails in 12-74% of pediatric patients with CF [21][22][23][24][25][26]. Some earlier studies using the stricter cut-off of the 15th BMI percentile to identify malnutrition support similar findings, with malnutrition being diagnosed in 20-30% of pediatric patients [27][28][29][30].…”
Section: Discussionmentioning
confidence: 78%
“…Most of the studies suggest that attaining a BMI below the 10th percentile (roughly corresponding to a z-score < −1.0) is indicative of malnutrition. With this in mind, published data suggest that malnutrition prevails in 12-74% of pediatric patients with CF [21][22][23][24][25][26]. Some earlier studies using the stricter cut-off of the 15th BMI percentile to identify malnutrition support similar findings, with malnutrition being diagnosed in 20-30% of pediatric patients [27][28][29][30].…”
Section: Discussionmentioning
confidence: 78%
“…A study conducted by Trapnell et al, demonstrated a correlation between adherence to PERT and increased body mass index (BMI) with a decrease in hospitalization rate, strengthening the observation that there is a close association between nutritional status and clinical outcomes. It is well known that in children with CF, reduced lung function is associated with an increased rate of hospitalization, and poor nutritional status, whereas a better nutritional status has a positive impact on lung function and survival rate [ 38 , 73 , 74 ].…”
Section: Treatmentmentioning
confidence: 99%
“…When compared to WFH/l and BMI z-scores, MUAC z-scores are considered to be more sensitive to diagnose mild-to-moderate malnutrition and to track the change in nutritional status overtime, and also to provide more reliable data in the presence of ascites or edema, being not affected by fluid shifts or hydration status ( Table 2 ) ( 43 , 51 , 55 , 56 ).…”
Section: The Significance Of Muac As a Single Datapoint Measurementmentioning
confidence: 99%